Microbiome diversity and reproductive incompatibility induced by the prevalent endosymbiont Arsenophonus in two species of African cassava Bemisia tabaci whiteflies. Issue 24 (1st December 2021) - El Hamss, Hajar; Ghosh, Saptarshi; Maruthi, M. N.; Delatte, Hélène; Colvin, John
Abstract: A minimum of 13 diverse whitefly species belonging to the Bemisia tabaci ( B. tabaci ) species complex are known to infest cassava crops in sub‐Saharan Africa (SSA), designated as SSA1‐13. Of these, the SSA1 and SSA2 are the predominant species colonizing cassava crops in East Africa. The SSA species of B. tabaci harbor diverse bacterial endosymbionts, many of which are known to manipulate insect reproduction. One such symbiont, Arsenophonus, is known to drive its spread by inducing reproductive incompatibility in its insect host and are abundant in SSA species of B. tabaci . However, whether Arsenophonus affects the reproduction of SSA species is unknown. In this study, we investigated both the reproductive compatibility between Arsenophonus infected and uninfected whiteflies by inter‐/intraspecific crossing experiments involving the sub‐group three haplotypes of the SSA1 (SSA1‐SG3), SSA2 species, and their microbial diversity. The number of eggs, nymphs, progenies produced, hatching rate, and survival rate were recorded for each cross. In intra‐specific crossing trials, both male and female progenies were produced and thus demonstrated no reproductive incompatibility. However, the total number of eggs laid, nymphs hatched, and the emerged females were low in the intra‐species crosses of SSA1‐SG3A+, indicating the negative effect of Arsenophonus on whitefly fitness. In contrast, the inter‐species crosses between the SSA1‐SG3 and SSA2 produced no female progeny and thus demonstrated reproductive incompatibility. The relative frequency of other bacteria colonizing the whiteflies was also investigated using Illumina sequencing of 16S rDNA and diversity indices were recorded. Overall, SSA1‐SG3 and SSA2 harbored high microbial diversity with more than 137 bacteria discovered. These results described for the first time the microbiome diversity and the reproductive behaviors of intra‐/inter‐species of Arsenophonus in whitefly reproduction, which is crucial for understanding the invasion abilities of cassava whiteflies. Abstract : The invasive SSA species of B. tabaci harbor diverse bacterial endosymbionts, many of which are known to manipulate insect reproduction. One such symbiont, Arsenophonus, is known to drive its spread by inducing reproductive incompatibility in its insect host and are abundant in SSA species of B. tabaci . This study showed that Arsenophonus decreased whitefly fitness and it is discussed with regard to whitefly microbiome.